Effect of plano-valgus foot posture on midfoot kinematics during barefoot walking in an adolescent population - Paolo Caravaggi; Chiarella Sforza; Alberto Leardini; Nicola Portinaro; Artemisia Panou (Journal of Foot and Ankle Research, 2018)
Abstract Background Plano-valgus is a common alteration of the paediatric foot, characterized by valgus hindfoot, foot pronation and drop of the medial longitudinal arch. Despite their importance in the diagnosis and classification of plano-valgus foot condition, little information is available on functional alterations of the major joints spanning the medial longitudinal arch – i.e. midtarsal and tarso-metatarsal. Aim of the study was to provide objective description of the alterations in plano-valgus midfoot joints with respect to those in an age-matched normally-developed feet population. Methods Twenty adolescents (13.3 ± 0.8 years) with bilateral plano-valgus feet underwent clinical examination and were gait-analysed via a validated 4-segment foot model. This allowed to measure static foot posture, kinematics of the main foot joints, and medial longitudinal arch deformation during walking at comfortable speed. Range of motion and temporal profiles of joint rotations were compared to those from a control population of age-matched adolescents with normally-developed feet. Results The plano-valgus midtarsal joint was more dorsiflexed, everted and abducted than that in the control group, and showed reduced sagittal-plane RoM (plano-valgus = 15.9 degrees; control = 22.2 degrees; P <  0.01). The tarso-metarsal joint was more plantarflexed and adducted, and showed larger frontal-plane RoM. The MLA showed larger RoM and was lower throughout the stance phase of the gait cycle. Conclusion Significant postural and kinematic alterations are present at the midtarsal and tarso-metarsal joints of adolescents with plano-valgus feet. Objective identification and quantification of plano-valgus foot alterations, via non-invasive gait-analysis, is relevant to improving the diagnosis of this condition and to evaluating the effect of conservative treatments and of surgical corrections by different techniques.